Combined strengthening method for critical heat flux and visual experiment device

By spraying water glass nanosolution on the boiling wall to form a nanoparticle plating layer, combined with a dropper device and a visual experimental device, the problem of increasing critical heat flow density in the existing technology is solved, and the efficient and low-cost boiling wall strengthening effect is achieved.

CN119510487APending Publication Date: 2025-02-25SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411712118.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively increase the critical heat flow density of boiling wall surfaces, and it is costly and complex in operation.

Method used

The water glass nano solution is sprayed on the boiling wall and heated to cure it to form a nanoparticle plating layer. On the basis of it, supercooled liquid is added dropwise using a dropper device, and precise measurement is performed in combination with a visual experimental device.

Benefits of technology

It significantly improves the hydrophilicity and critical heat flow density of boiling walls, is cheap and easy to operate, can be quickly applied to boiling walls of different materials, and has a significant stacking and strengthening effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119510487A_ABST
    Figure CN119510487A_ABST
Patent Text Reader

Abstract

The invention relates to a combined strengthening method of critical heat flux density and a visual experiment device, after a water glass nano solution is uniformly sprayed on a boiling wall surface, the water glass nano solution is further heated until the water glass nano solution on the boiling wall surface is bubbled and solidified on the boiling wall surface, a nano-particle coating is obtained after polishing, a specific dropper device is adopted in the boiling process, and the water glass nano solution on the boiling wall surface is solidified on the boiling wall surface. The supercooled liquid is dropwise added on the boiling wall surface, the critical heat flux is accurately measured by adopting a visual experimental device, and the critical heat flux strengthening mechanism is verified by shooting images. The prepared nano-particle coating is high in porosity, the hydrophilicity of the boiling wall surface can be remarkably improved, the dropper device is simple in structure and low in cost, formation of irreversible dry spots can be inhibited, and the critical heat flux density is improved through the superposition effect of the two methods. The device is low in cost, easy and convenient to operate, high in expansibility and capable of being rapidly applied to boiling wall surfaces made of different materials. A pool boiling experiment device is adopted as the visual experiment device, and the mechanism and the effect of critical heat flux density strengthening are verified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a technology in the field of heat transfer enhancement, in particular to a combined enhancement method for critical heat flux density and a visual experimental device. Background Art

[0002] The critical heat flux is an important indicator to measure the heat transfer performance of the boiling wall, and the surface characteristics of the boiling wall such as the vaporization core density and wettability and the liquid flow have an extremely important influence on the critical heat flux. Therefore, by making a coating or adding a dropper on the boiling wall, the critical heat flux can be significantly enhanced. Summary of the invention

[0003] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a combined enhancement method for critical heat flux and a visualization experimental device. The prepared nanoparticle coating has high porosity and can significantly improve the hydrophilicity of the boiling wall. The dropper device has a simple structure and low cost, and can inhibit the formation of irreversible dry spots. The superposition effect of the two methods improves the critical heat flux. It is low-cost, easy to operate, and has strong scalability, and can be quickly applied to boiling walls of different materials. The visualization experimental device uses a pool boiling experimental device to verify the mechanism and effect of critical heat flux enhancement.

[0004] The present invention is achieved through the following technical solutions:

[0005] The invention relates to a combined strengthening method for critical heat flux density. After a water glass nano solution is uniformly sprayed on a boiling wall surface, the water glass nano solution on the boiling wall surface is further heated until the water glass nano solution on the boiling wall surface bubbles and solidifies on the boiling wall surface, and a nano particle coating is obtained after polishing. During the boiling process, a specific dropper device is used to drop a supercooled liquid on the boiling wall surface, and a visual experimental device is used to accurately measure the critical heat flux density. By taking images, the critical heat flux density strengthening mechanism is verified.

[0006] The solvent in the water glass nano solution is water glass solution, and the solute is nano particles, wherein the water glass solution is potassium water glass or sodium water glass; and the nano particles are silicon oxide, aluminum oxide, titanium dioxide, zirconium oxide, copper oxide, carbon or silver particles.

[0007] The solute component of the potassium water glass is industrial potassium silicate, and the molecular formula is K2O·nSiO2·mH2O; the solute component of the sodium water glass is industrial sodium silicate, and the molecular formula is Na2O·SiO2·mH2O.

[0008] The particle size of the nanoparticles is less than 100 nm.

[0009] The boiling wall is a smooth wall with weak hydrophilicity, and available materials include various metals (such as copper, iron, stainless steel, aluminum alloy, etc.) and non-metals (glass, silicon wafer, ceramic, microcrystalline, enamel, sapphire, etc.).

[0010] The dropper device drips supercooled liquid onto the boiling wall surface through a liquid supply unit and a needle tube, and the liquid supply unit can be a pump or a water storage tank. Technical Effects

[0011] The present invention applies water glass nano-solution to prepare nano-particle coating on boiling wall surface, so as to improve the hydrophilicity of the wall surface and strengthen the critical heat flux density; on the basis of the nano-particle coating, a dropper device is added on the boiling wall surface; after strengthening, the mechanism and effect of strengthening the critical heat flux density are verified by using a visual experimental device. Compared with the prior art, the nano-particle coating for strengthening the critical heat flux density prepared by the present invention has a micron-level thickness, high porosity, and micron-level and nano-level morphological characteristics, which can significantly improve the hydrophilicity of the boiling wall surface, and then improve the critical heat flux density; the dropper device in the above method can further achieve superposition strengthening of the critical heat flux density on the basis of the nano-particle coating; the visual experimental device in the above method can accurately measure the critical heat flux density and verify the strengthening mechanism by taking images. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It is a flow chart of the present invention;

[0013] Figure 2 It is a schematic diagram of the visualization experimental device of the present invention;

[0014] Figure 3 This is a schematic diagram of the heater in Example 1;

[0015] Figure 4 This is the dry spot image of Example 1;

[0016] Figure 5 This is the dry spot image of Example 2;

[0017] Figure 6 , Figure 7 The morphology image of the nanoparticle coating on the surface of the quartz glass in Example 2 obtained by scanning electron microscopy;

[0018] Figure 8 , Fig. 9 , Fig.10 Schematic diagram of the dropper device for enhancing critical heat flux density described in Example 3. DETAILED DESCRIPTION Example 1

[0019] like Figure 2 and Figure 3As shown, this embodiment involves a visualization experimental device for enhancing critical heat flux density, including: a heater 1, a pool boiling container 2, a copper electrode 3, a light source 4, and a high-speed camera 7, wherein: the heater 1 is arranged at the bottom of the pool boiling container 2, and the conductive film arranged at the bottom of the heater 1 is connected to the power supply through the conductive silver glue and the copper electrode 3, the spectrometer 5 and the plane mirror 6 are arranged in sequence below the pool boiling container 2, the light emitted by the light source 4 is reflected by the spectrometer 5, and is used as the incident light to vertically irradiate the boiling wall surface, the reflected light is transmitted by the spectrometer 5 and reflected by the plane mirror 6, and the high-speed camera 7 collects the reflected light to obtain a dry spot image for verifying the critical heat flux density enhancement mechanism.

[0020] like Figure 3 As shown, the heater 1 is a quartz glass with a conductive film on one side, and the quartz glass surface without the conductive film is in contact with the working medium as a boiling wall; a heat flux density is provided for the boiling wall, and a critical heat flux density is obtained by gradually increasing the power of the power supply.

[0021] After specific practical experiments, this embodiment uses saturated deionized water as the working fluid and sets the critical heat flux density of the original surface of the quartz glass to 0.85MW / m 2 , the measurement accuracy reaches 0.05MW / m 2 , to meet the needs of general scientific research or engineering applications; such as Figure 4 As shown, the captured images clearly show the proportion of dry spots on the wall, which can be used to verify the enhancement mechanism of the critical heat flux density.

[0022] Compared with the existing technology, this device uses conductive silver glue to connect the conductive film and the copper electrode, achieving the effects of stable connection, strong conductivity and low cost, which is conducive to improving the measurement accuracy of critical heat flux density. Example 2

[0023] This embodiment relates to a method for preparing a nanoparticle coating for strengthening the critical heat flux density on the surface of quartz glass, which specifically includes:

[0024] 1) Using an alcohol cotton pad to clean the quartz glass sheet, the quartz glass sheet is preferably a 50 mm×50 mm uniform sheet, which has a smooth surface and weak hydrophilicity and can be used as the initial boiling wall;

[0025] 2) preparing a water glass nano solution by mixing aluminum oxide nanoparticles with sodium water glass, spraying the solution evenly on the surface of the quartz glass heater without the conductive coating, and letting it stand for about 1 hour;

[0026] 3) placing the quartz glass heater in a high temperature environment of about 300° C. for 1 hour, wherein the high temperature environment is preferably a muffle furnace capable of controlling a rated temperature;

[0027] 4) After the boiling wall morphology reaches stability, it is polished to retain only a thin layer of nanoparticle coating;

[0028] 5) Repeat steps 2 to 4 until the nanoparticle coating completely covers the boiling wall surface;

[0029] 6) Add deionized water to the boiling wall, observe the contact angle, and confirm that the hydrophilicity is good (the contact angle is close to zero);

[0030] 7) Using a scanning electron microscope to obtain a morphological image of the nanoparticle coating on the surface of the quartz glass;

[0031] 8) Using the visualization experimental device described in Example 1, measure the critical heat flux density of the quartz glass surface on which the nanoparticle coating has been prepared, and take a dry spot image.

[0032] like Figure 6 and Figure 7 As shown in the figure, after specific practical experiments, it can be observed using a scanning electron microscope that the nanoparticle coating on the surface of the quartz glass has porous characteristics, indicating that its water absorption properties are enhanced; the critical heat flux density of the quartz glass surface with nanoparticle coating is ~1.6MW / m 2 , compared with the original surface of quartz glass, the critical heat flux density strengthening effect can reach 88%; Figure 5 As shown, the proportion of dry spots in the captured images is significantly reduced, indicating that the key mechanism of critical heat flux density enhancement is that the nanoparticle coating inhibits the expansion of dry spots.

[0033] Compared with the existing technology, this method applies water glass nano-solution to prepare boiling wall nano-particle coating to improve the wall hydrophilicity and enhance the critical heat flux density; for the first time, a visualization method is used to observe the dry spots on the nano-particle coating to verify the enhancement mechanism of the critical heat flux density. Example 3

[0034] like Figure 8 As shown, compared with Example 1, a needle tube 8 and a liquid supply unit 10 connected thereto are provided above the heater 1 in this embodiment, wherein the heater 1 is quartz glass with a nanoparticle coating prepared by the method of Example 2.

[0035] The pool boiling container 2 is filled with sufficient deionized water, and a hole is opened on the top to facilitate the needle tube 8 and the hose 9 to pass through, ensuring that the needle tube points vertically to the boiling wall surface, so that the distance between its tip and the boiling wall surface is as small as possible.

[0036] The liquid supply unit 10 described in this embodiment is a pump fixedly arranged on the pool boiling container 2, and its function is to absorb the supercooled liquid through the hose 9 and transport the supercooled liquid to the boiling wall through the needle tube 3, so that the dry spot area is moistened and the formation of irreversible dry spots is inhibited. Fig. 9 A submersible pump placed in water as shown, or Fig.10 The water storage tank shown has a certain pressure head and transports the liquid to the heated wall surface through gravity.

[0037] After specific practical experiments, under the condition of saturated deionized water as the working fluid, the supercooled liquid was dripped at a rate of about 6.3 g / s, and the critical heat flux density was obtained by gradually increasing the power supply power, so that the critical heat flux density of the quartz glass surface was 2.6 MW / m 2 , the total effect of superimposed reinforcement reaches 206%.

[0038] Compared with the prior art, the present invention combines the nanoparticle coating and the dropper to achieve superposition enhancement of the critical heat flux density.

[0039] The above-mentioned specific implementation can be partially adjusted in different ways by those skilled in the art without departing from the principle and purpose of the present invention. The protection scope of the present invention shall be based on the claims and shall not be limited by the above-mentioned specific implementation. Each implementation scheme within its scope shall be subject to the constraints of the present invention.

Claims

1. A combined strengthening method for critical heat flux density, characterized in that: After the water glass nano solution is evenly sprayed on the boiling wall, it is further heated until the water glass nano solution on the boiling wall bubbles and solidifies on the boiling wall. After polishing, a nanoparticle coating is obtained. During the boiling process, a specific dropper device is used to drip supercooled liquid on the boiling wall, and a visualization experimental device is used to accurately measure the critical heat flux density. By taking images, the critical heat flux density enhancement mechanism is verified.

2. The combined strengthening method of critical heat flux according to claim 1 is characterized in that: The solvent in the water glass nano solution is water glass solution, and the solute is nano particles, wherein the water glass solution is potassium water glass or sodium water glass; and the nano particles are silicon oxide, aluminum oxide, titanium dioxide, zirconium oxide, copper oxide, carbon or silver particles.

3. The combined strengthening method of critical heat flux according to claim 1 is characterized in that: The visualization experimental device comprises: a heater, a pool boiling container, a copper electrode, a light source and a high-speed camera, wherein: the heater is arranged at the bottom of the pool boiling container, a conductive film is arranged on one side of the heater and is connected to a power source through a conductive silver glue and a copper electrode, a spectroscope and a plane mirror are arranged in sequence below the pool boiling container, the light emitted by the light source is reflected by the spectroscope and vertically irradiates the boiling wall surface as incident light, the reflected light is transmitted by the spectroscope and reflected by the plane mirror, and the high-speed camera collects the reflected light to obtain a dry spot image for verifying the critical heat flux density enhancement mechanism; A needle tube and a liquid supply unit connected thereto are arranged above the heater, wherein one side of the heater is a boiling wall surface on which a nano-particle coating is arranged.

4. The combined strengthening method of critical heat flux according to claim 2 is characterized in that: The solute component of the potassium water glass is industrial potassium silicate; the solute component of the sodium water glass is industrial sodium silicate.

5. The combined strengthening method of critical heat flux according to any one of claims 1 to 3, characterized in that: The particle size of the nanoparticles is less than 100 nm.

6. The combined strengthening method of critical heat flux according to claim 1 or 3, characterized in that: The boiling wall surface is a smooth wall surface with weak hydrophilicity, and is made of copper, iron, stainless steel, aluminum alloy, glass, silicon wafer, ceramic, microcrystalline, enamel or sapphire.

7. The combined strengthening method for critical heat flux according to any one of claims 1 to 6, characterized in that: include: 1) Use alcohol cotton pads to clean the quartz glass sheet as the boiling wall; 2) preparing a water glass nano solution by mixing aluminum oxide nanoparticles with sodium water glass, and spraying the solution evenly on the surface of the quartz glass heater without the conductive coating and letting it stand; 3) Place the quartz glass heater in a 300°C environment; 4) After the boiling wall morphology reaches stability, it is polished to retain only a thin layer of nanoparticle coating; 5) Repeat steps 2 to 4 until the nanoparticle coating completely covers the boiling wall surface; 6) Add deionized water to the boiling wall surface and observe the contact angle to confirm that the hydrophilicity is good, that is, the contact angle is close to zero; 7) Using a scanning electron microscope to obtain a morphological image of the nanoparticle coating on the surface of the quartz glass; 8) Measure the critical heat flux density of the quartz glass surface on which the nanoparticle coating has been prepared, and take a dry spot image.

Citation Information

Cited By

  • Self-circulation two-phase liquid cooling heat dissipation device for high-energy electronic component

    CN121262787A